PERANAN INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) DALAM MENGEMBANGKAN PARIWISATA DANAU TOBA “MONACO OF ASIA” - Arwin Tannuary; Ambo Enre (Politeknik Bisnis Indonesia, 2021)
Lake Toba is one of the largest caldera lakes in the world, located in North Sumatra Province, Mel176 km to the west of Medan City. Lake Toba, which is one of the super priority tourist destinations that has been certified by UNESCO Global Geopark (UGG) at the world level. This provides a huge opportunity and responsibility for Indonesia, in advancing the economy and sustainable development in the area around Lake Toba. This study discusses the extent of the Role of Information and Communication Technology (ICT) in Developing Lake Toba Tourism as the